Streetwise, Active and Cool: How Do Vilnius Adolescents Perceive Their Peers’ Linguistic Identity? - Čekuolytė, Aurelija (Taikomoji kalbotyra, 2014)
The current sociolinguistic enterprise is preoccupied with the local meaning of the linguistic resources, however, the global meaning is equally important, because any linguistic resource becomes socially meaningful only when it is recognized as such by the others. Therefore, the main objectives of this article are (1) to advocate for the need to investigate not only the local meaning, discovered through the in-depth ethnographic fieldwork, but also the global meaning of the linguistic resources, (2) to demonstrate how by inclusion of other methodologies, in this case, the verbal guise technique, we can investigate the global meaning of the ethnographically derived data, and (3) to present results of the study of Vilnius adolescents’ perception of their peers’ linguistic identity which encompassed these two methodologies. During the course of the fieldwork in a school in Vilnius, five main social categories of Vilnius adolescents were distinguished: active schoolwise girls, cool girls, cool boys, streetwise girls, and streetwise boys. Different linguistic resources are incorporated in construction of different adolescents’ social categories. But are those linguistic differences local or could they be recognized as having this particular social meaning in other communities of practice? In order to answer this question, the verbal guise experiment was conducted in 3 other schools. Most of the adolescents’ identities were recognized by the adolescents in the verbal guise experiment. This implies that the linguistic variation, involved in the identity construction, has the same meaning in Vilnius dormitory neighborhoods.